The Effect Of Product Quality, Features, Word Of Mouth And E-Commerce On Purchase Decisions - Shochibul Mighfar; Sukaris Sukaris; Moch. Saleh; Ahmad Qoni Dewantoro (Universitas Muhammadiyah Gresik, 2020)
This study aims to examine the Effect of Product Quality, Features, Word of Mouth and E-commerce on Xiaomi smartphone purchasing decisions. This type of research is quantitative research. The sampling technique uses accidental sampling technique with a total sample of 100 consumers who are members of the MI community application. To analyze the relationship between dependent and independent variables is multiple linear regression with classic assumption test (normality test, multicollinearity test, and heteroscedasticity test), hypothesis test (t-test and F test), and also model test (test coefficient of determination). The results of the t-test indicate that product quality and features influence the Xiaomi smartphone purchase decision with a significance level (0,000 and 0.005), word of mouth and e-commerce have no effect on Xiaomi smartphones with a significance level (0.311 and 0.568). Simultaneous results with the F test, product quality, features, word of mouth and e-commerce simultaneously influence the purchase decisions of Xiaomi smartphones. The determination coefficient shows that the Adjusted R Square value is 0.974 that product quality, features, word of mouth and e-commerce can be explained by the independent variable of 97.4%, while the rest is explained by other factors.